2023
DOI: 10.1002/ecy.4041
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration strategies and forest resilience to changing fire regimes: Insights from a Goldilocks model

Abstract: Disturbances are ubiquitous in ecological systems, and species have evolved a range of strategies to resist or rebound following disturbance. Understanding how the presence and complementarity of regeneration traits will affect community responses to disturbance is increasingly urgent as disturbance regimes shift beyond their historical ranges of variability. We define “disturbance niche” as a species' fitness across a range of disturbance sizes and frequencies that can reflect the fundamental or realized nich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…We can merely say that our estimate represents a lower limit on the current risk of this species. Interestingly, Ramiadantsoa et al (2023) developed a simulation of serotinous species persistence in a stand-replacing fire regime and found that monocultures were extirpated at a fire rotation of around 20 years, not much less than the minimum cycle estimate we examined here. Nonetheless, a comparison of the likelihood of persistence across sites and species clearly depends on the time to reach reproductive maturity, which in turn depends on site productivity.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We can merely say that our estimate represents a lower limit on the current risk of this species. Interestingly, Ramiadantsoa et al (2023) developed a simulation of serotinous species persistence in a stand-replacing fire regime and found that monocultures were extirpated at a fire rotation of around 20 years, not much less than the minimum cycle estimate we examined here. Nonetheless, a comparison of the likelihood of persistence across sites and species clearly depends on the time to reach reproductive maturity, which in turn depends on site productivity.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, a fire history study in mixed-conifer forests upslope to one of our Whiskeytown study sites had a much shorter fire cycle of 8 years (Fry & Stephens, 2006), which may indicate a higher probability of more frequent fires in the adjacent knobcone pine ecosystems in this region. It is important to point out our sample size was relatively small and does not accurately represent the full variability of knobcone pine across its entire range, but it fits the findings of Ramiadantsoa et al (2023), who report that the risk of extirpation in serotinous conifers drastically decreases between a 20-and 50-year fire cycle. Finally, given that the fire cycle is predicted to shorten in the western United States, inspection of Figure 8 means that our optimism about the resilience of this species must be guarded.…”
Section: Discussionmentioning
confidence: 81%